Pengaruh Work Life Balance, Disiplin Kerja dan Lingkungan Kerja terhadap Kinerja Karyawan pada PT PrimaJaya Putra Sentosa - Putri, Dea Marliana; Muttaqin, Ridlwan; Riadi Akbar, Ridho (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to analyze the effect of work life balance, work discipline and work environment on employee performance at PT PrimaJaya Putra Sentosa. This study uses a quantitative research method through a descriptive and verification approach, questionnaires were distributed to 35 employees. The research sample of 35 employees was taken using a purposive sampling technique. Data analysis methods used in this study include descriptive analysis, verification analysis (hypothesis testing), determination coefficient analysis, all of which are carried out using SPSS version 26 software. This analysis aims to describe the data, test the truth of the hypothesis, and measure the strength of the relationship between variables. The results of the study indicate that the work-life balance and work environment variables have a positive and significant relationship with employee performance, while the work discipline variable does not show a significant relationship.